PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 24 KUALA PENASO KECAMATAN PINGGIR - Syarifuddin '; Mahmud Alpusari; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research aims to improve the learning process and improve learning outcomes sains of fourth grade students of SDN 24 Kuala Penaso Kecamatan Pinggir by implementing cooperative learning model Think Pair Share (TPS). The research subjects were fourth grade students who have the heterogeneous academic ability. This research is a class act with two cycles. Each cycle consisted of two meetings learning process and one-time Daily Deuteronomy (UH) which was held at the end of each cycle. This study also consists of four stages, namely planning, implementation, observation and reflection. This research presents the results obtained each before the implementation an improve in base score sycle with the average being 65, In the first cycle improve an average of 75,31 with increase as 15.86% and an impove in the second with an average of 84,69 with increase as 30,29%. The results of this study indicate that the implementing of cooperative learning model TPS can improve the process of learning sains and improve learning outcomes of fourth grade students of SDN 24 Kuala Penaso Kecamatan Pinggir of the full semester of the academic year 2015/2016. Key Words : Learning Process, Sains Outcomes Learning, Cooperative Learning, Tipe Think Pair Share (TPS), Classroom Action Result.